(untitled) (Journal of Nepal Geological Society, 2025)
The present research work deals with the petrographic analysis of the Tista sand deposits which is exposed along the river bank and point bars. The constituent minerals of the sand deposits are quartz (73.18%), microcline (8.10%), orthoclase (0.15%), plagioclase (1.16%), lithic grains (1.37%), muscovite (6.59%), biotite (3.67%), heavy minerals, organic matters, minor amounts of matrix whereas fine-grained quartz and clay constitute the matrix materials. The heavy minerals include pyroxene, amphiboles, zircon, tourmaline, garnet, chlorite and opaque minerals. The major minerals and the lithic grains can be expressed as quartz>feldspar>lithic grains using the QFL ternary diagram. Among the heavy minerals, garnet is the most abundant mineral. The presence of magnetite was established using its magnetic susceptibility. Ninety-two percent of the sand specimens have the mineralogical index value ranging from 80 to 100, which suggests that the Tista sand deposits were derived from an extremely weathered condition. The QPK (Quartz-Plagioclase-K-feldspar) ternary plot reveals that all the sand samples fall near the Quartz-apex and the prevalence of more stable K-feldspar over the less steady plagioclase feldspar. The bivariate diagram of ln(Q/R) versus ln(Q/F) suggests the metamorphic provenance for the investigated sand deposits. The Q/(F+L) vs Qp/(F+L) plot indicates that the humid climatic conditions prevailed during the deposition these sand deposits.